CHALLENGES AND STRATEGIES ON IMPLEMENTING AN ECOLOGICAL CORRIDOR BETWEEN PROTECTED AREAS IN CERRADO BIOME - Samuel Fernando Schwaida; Rejane Ennes Cicerelli; Tati de Almeida; Henrique Llacer Roig (Revista Árvore, 2018)
ABSTRACT Landscape management aiming to reconnect isolated vegetation patches through corridors is important to mitigate impacts on fauna and flora species due to habitat degradation and fragmentation. This work presents a methodology based on geoprocessing tools to define ecological corridors. This case study was conducted on Distrito Federal, central Brazil, aiming to propose a corridor for large and mediumsized mammals reconnecting Águas Emendadas Ecological Station and Formosa Military Training Area. Cost analysis using geoprocessing tools and available official database generated three paths (A, B, C) Extension varied from 28.88 (A) to 47.34 km (C) and paths intersection with natural vegetation patches varied from 74.43 (A) to 90.35% (B). Intersection with potential Permanent Preservation Areas (APPs) varied from 66.32 (A) to 86.26% (C). Overlap with private properties registered on Rural Environmental Registry (CAR) was verified for best paths A and B and revealed 51.60% and 50.97% of overlap. Cost analysis tools and AHP were considered efficient for generating ecological corridors.